FORMATION OF EDUCATIONAL PARTICIPANTS’ READINESS TO MANAGE INNOVATIVE PROCESSES AT GENERAL SECONDARY EDUCATION INSTITUTIONS AS A PEDAGOGICAL PROBLEM: THEORETICAL OVERVIEW - Svitlana M. Nadtochii (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
The article focuses on the need to introduce pedagogical innovations in the school educational process. A reason has been established for the insufficient level of psychological readiness of teachers to use innovation in the school informational and educational environment. A definitional analysis of the concepts of «informational and educational environment», «innovation activity», «readiness for innovation» was imlemented. Comparative characteristics of traditional and innovative educational models are given. Based on the analysis of scientific literature, we proposed our own interpretation of the phenomenon of teacher’s readiness for innovation. The main directions of innovative activity of the teacher are defined: innovations in education, education, management, retraining of personnel. The need to have certain abilities that contribute to the formation of the readiness of teachers of the institution of general secondary education to innovate within the framework of the competentcy approach was noted. It is stated that the management of innovation activities in general secondary education institutions is a targeted activity of management entities at various levels. The functions of the informational-educational environment are disclosed in order to implement the requirements of educational standards. It was noted that the strategic task of developing school education in modern conditions is to update the content, forms and methods, achieve a new quality of its results. It is emphasized that the main factors affecting the development of education in modern conditions are the appeal to the personality of students and the consideration of the individual trajectory of the development of their competencies. An attempt was made to identify factors that contribute to the effective formation of the readiness of educational participants to manage innovative processes in school. We consider the teacher's readiness for innovative activity as a complex personal and professional education of teachers, determining their focus on the development of their own professional activity, the activity and independence of assimilation, creative implementation, the creation of new ways, techniques of pedagogical work that have an innovative orientation.